2018
DOI: 10.3390/molecules23102554
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Indole-Derived Thioureas

Abstract: A series of 2-(1H-indol-3-yl)ethylthiourea derivatives were prepared by condensation of 2-(1H-indol-3-yl)ethanamine with appropriate aryl/alkylisothiocyanates in anhydrous media. The structures of the newly synthesized compounds were confirmed by spectroscopic analysis and the molecular structures of 8 and 28 were confirmed by X-ray crystallography. All obtained compounds were tested for antimicrobial activity against Gram-positive cocci, Gram-negative rods and for antifungal activity. Microbiological evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Antitumoral [ 21 , 22 ], anti-arrhythmic [ 19 ], anti-inflammatory [ 23 ], antimicrobial [ 24 ], and antihypertensive properties are amongst the reported biological activities. The synthesis of indole derivatives is largely explored due to relevant biological applications described for this scaffold, and there are reports on the synthesis of indole hybrids [ 25 , 26 , 27 ]. We thought it would be interesting to obtain chromene-indole hybrids, so we studied the reaction of 2-aryl-4-chloro-2 H -chromene-3-carbaldehydes 2a – c with indole ( 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Antitumoral [ 21 , 22 ], anti-arrhythmic [ 19 ], anti-inflammatory [ 23 ], antimicrobial [ 24 ], and antihypertensive properties are amongst the reported biological activities. The synthesis of indole derivatives is largely explored due to relevant biological applications described for this scaffold, and there are reports on the synthesis of indole hybrids [ 25 , 26 , 27 ]. We thought it would be interesting to obtain chromene-indole hybrids, so we studied the reaction of 2-aryl-4-chloro-2 H -chromene-3-carbaldehydes 2a – c with indole ( 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of thiourea derivatives 1 and 3 was described previously . The molecular structure of 3 has been determined.…”
Section: Methodsmentioning
confidence: 99%
“…SAR studies reported the importance of 4bromophenyl moiety. All the compounds, (38) (EC 50 = 8.7 ± 0.4 μM) was found to be highly potent as compared to standard drug efavirenz (EC 50 = 0.002 ± 0.0002 μM) 114 . In 2016, Doussan et al, reported synthesis and evaluation of various indole derivatives for anti-HIV activity.…”
Section: Fig 4: Anti-malarial Activity Of Indole Derivativesmentioning
confidence: 97%
“…Sanna and his colleagues mentioned the synthesis of indolethiourea hybrids and evaluated it against a pool of microbes containing both Gram-positive and Gramnegative types. Compound (1) (minimum inhibitory concentration as MIC (minimum inhibitory concentration) < 12.5 μg/mL) was establish to be extremely potent as compared with standard drug ciprofloxacin (MIC < 1.0 μg/mL) 53 .…”
Section: Evaluation Of Indole Compoundsmentioning
confidence: 99%